Konsep Etika Peserta Didik Dalam Pendidikan Islam Menurut Syekh Burhanuddin Al-Zarnuji - Novita Sari Br Siregar, Muhammad Saleh, Ahmad Fuadi (Khazanah : Journal of Islamic Studies, 2023)
In this study the author presents the ethical concept of students according to Syekh Burhanuddin Al-Zarnuji as contained in the book of Ta'lim Al-Muta'allim to further study its relevance to current social conditions. This research is a library research. Data analysis was carried out by means of inductive-deductive, comparative, descriptive and interpretive. The results of the study explain the ethical concepts of students in Islamic education in general divided into: the ethics of students towards themselves, the ethics of students in seeking knowledge, the ethics of students towards teachers and ethics in educational institutions. The concept of student ethics according to Syekh Burhanuddin Al-Zarnuji is contained in the Book of Ta'lim al-Muta'allim Tariq al-Ta'allum which explains the ethics of participants includes six things, namely the ethics of students towards God, the ethics of students towards their parents, the ethics of students students towards educators, students' ethics towards books, students' ethics towards themselves, students' ethics towards friends, students' ethics when studying. Of the several ethical concepts offered by Syekh Burhanuddin Al-Zarnuji most of them are still relevant to current social conditions but there are several concepts that need new changes and innovations, especially in the relationship between students and educators who seem to be unidirectional so as to create learning centered on teacher only. This needs to change so that learning becomes student-centered as well.